JURIDICAL ANALYSIS OF DIGITAL VIOLENCE BY CHILDREN IN THE PHENOMENON OF "CONTENT BRAWLS" (CASE STUDY AT KESAMBI POLICE STATION, CIREBON CITY) - Ricko Satriatama; Adib Adib; Fadlilyani Ainusyamsi; Anom Sutrisno (Jurnal Abdisci, 2025)
Abstract Background. The phenomenon of "content brawls" involving minors has become a new form of digital violence that threatens social security and public order. This behavior impacts the immediate victim and worsens public perception through massive dissemination on social media. Aims. This study aims to determine the legal consequences of digital violence carried out by children in the context of content brawls and the police's prevention and handling efforts in cases of digital violence against children in content brawls. Methods. The method used is normative juridical by using secondary data as primary data, such as laws and regulations, literature studies, and documentary studies, as well as primary data as supporting data, such as interviews with the police. Result. The results of the study show that there are legal loopholes in the handling of digital violence by children that have not been fully regulated by law, especially in the context of proving malicious intent (mens rea) and protection of perpetrators who are still classified as children, so that the handling of cases by the Kesambi Police shows a tendency to use a non-penal approach that prioritizes restorative justice, under the principle of the best interest of the child. Conclusion. Efforts such as Police Go To School, routine raids, and collaboration with local communities are concrete steps in preventing similar cases. Implementation. This study recommends formulating special policies related to the management of digital violence against children based on the principles of child protection without neglecting aspects of justice and prevention.